LINGUODIDACTIC APPROACH OF COMPARATIVES - To`lqinova Charos Davron qizi; Abdurahmonova Zilola Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This paper explores the linguistic and didactic aspects of teaching comparatives in language education. It discusses various linguistic theories and approaches to teaching comparatives and analyses their effectiveness in facilitating language acquisition. Additionally, the paper examines the didactic strategies and methods employed in teaching comparatives and their impact on students' learning outcomes. The study aims to provide insights into the linguistic and didactic considerations of teaching comparatives, with the goal of enhancing language education practices and promoting effective language acquisition.